Pengaruh Likuiditas, Leverage, dan Profitabilitas Terhadap Pengungkapan Sustainability Report - Toni Hermawan; Sutarti Sutarti (Institut Bisnis dan Informatika Kesatuan, 2021)
One of the main objectives of the establishment of an entity is to achieve business continuity or sustainability in the future, a good company is always able to manage in terms of financial and non-financial. Business activities that are only profit-oriented without paying attention to the surrounding conditions will not be able to bring the company to business continuity in the future. In this case, although banking in its business activities does not directly intersect with nature, the sustainability of a company is assessed through three important aspects that become the benchmark for sustainability, one of which is economic value. The economic value of banking can be said to be very material for disclosing a sustainability report (Sustainability Report), which in this sustainability report encourages the achievement of Sustainable Development Goals for the welfare of the company's stakeholders and does not have a negative impact on the community and the environment around the company. This study aims to analyze the effect of Liquidity, Leverage, and Profitability on the disclosure of the Sustainability Report in Banking Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2020 period. Profitability as an independent variable, Liquidity is proxied by the Current Ratio (CR), Leverage as an independent variable is proxied by the Dept to Assets Ratio (DAR), and Profitability is proxied by Return On Assets (ROA) while the Sustainability Report is proxied by the Sustainability Report Disclouser Index. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the period 20117-2020. The sample selection method is purposive sampling method. A total of 11 companies were used as research samples for 4 years. The data in this study were obtained through the website www.idnfinancials.com to obtain the annual financial report and through the company website to obtain the company's sustainability report. Hypothesis testing in this study using multiple linear regression method. The results showed that partially liquidity and leverage had no effect on the disclosure of the sustainability report, and profitability had a significant negative effect on the disclosure of the sustainability report. Simultaneously liquidity, leverage, and profitability affect the disclosure of the sustainability report. Keywords: Liquidity, Leverage, Profitability, Sustainability Report